CHALLENGES AND OPPORTUNITIES IN THE IMPLEMENTATION OF STRENGTHENING CHARACTER EDUCATION IN EFL CLASSROOM - Ike Purnamasari; Nuraeni . (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2021)
Strengthening Character Education is an educational program in schools to strengthen students' character with moral values. The Indonesian government launched this program to faced students’ moral degradation. As the country that used English as a Foreign Language (EFL), this study investigates the challenges faced by a teacher in the implementation of Strengthening Character Education in the EFL classroom and to know teacher strategy to change the challenges become opportunities. This study conducted a case study of the EFL teacher in Junior High School. The data collection consisted of classroom observation, interview, documentation, and data triangulation. The findings gained, the teacher has implemented several character values in the EFL classroom activities. The teacher faced challenges coming from the students, learning situations, and learning materials. For the opportunities, there was classroom management and being a role model.